Marine Biogenic Minerals Hold Clues About Changes in Ocean Chemistry and Climate: Some Important Lessons Learned from Studies of Stable and Radioactive Isotopes of Be and Al - Devendra Lal (The Scientific World Journal)
The elements Be and Al exhibit very short residence time in ocean waters, and therefore serve as useful tracers for the study of biogeochemical processes in seawater. A unique feature of these tracers is that nuclear interactions of cosmic rays in the atmosphere produce appreciable amounts of two radioactive isotopes, 10Be (with a half-life of 1.5 my) and 26Al (with a half-life of 0.7 my), which are introduced in the hydrosphere, cryosphere, and lithosphere via precipitation. Thus, these elements are labeled by their respective radioactive isotopes, which help quantitative tagging of their biogeochemical cycles. Finally, as we report here, several marine organisms incorporate them in their skeletal shells in certain fixed proportions to their concentrations in the seawater, so that it seems possible to study changes in the ocean chemistry and climate over the past several million years. We summarize here the recent discovery by Dong et al.[9] of significant enrichments of intrinsic Be and Al in marine foraminiferal calcite and coral aragonite, and of Al in opal (radiolarians) and aragonite (corals), which should make it possible to determine 10Be/Be and 26Al/Al in oceans in the past. We also summarize their measured 10Be/9Be in foraminiferal calcite in Pacific Ocean cores, which reveal that the concentrations and ratios of the stable and cosmogenic isotopes of Be and Al have varied significantly in the past 30 ky. The implications of these results are discussed.